2009
DOI: 10.1016/j.compedu.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Creative use of podcasting in higher education and its effect on competitive agency

Abstract: This paper describes an academic experience of podcasting, which involved a group of students of a course on multimedia communication and human-computer interaction. These students acted both as users of the university's podcasting service, and as creators of podcasted lessons. A comprehensive analysis based on the evaluation of the effects on student performance, on data from student satisfaction surveys, from interviews and from instructors' observations provided encouraging results: full-time students co-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
2
22

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 16 publications
(16 reference statements)
4
92
2
22
Order By: Relevance
“…Podcasts supply educational content in a format that is fitting to the student needs as it is available whenever and wherever the student wants (Lazzari, 2009). The mobility of learning is considered as an advantage of podcasting although students can also choose to listen to podcasts on a computer in a "study-like" environment (McKinney, & Page, 2009).…”
Section: Podcasting Technologymentioning
confidence: 99%
“…Podcasts supply educational content in a format that is fitting to the student needs as it is available whenever and wherever the student wants (Lazzari, 2009). The mobility of learning is considered as an advantage of podcasting although students can also choose to listen to podcasts on a computer in a "study-like" environment (McKinney, & Page, 2009).…”
Section: Podcasting Technologymentioning
confidence: 99%
“…Aliotta et al 2008;Cane and Cashmore 2008;Chan and Lee 2005;Draper and Maguire 2007;Lazzari 2009;Stewart and Doolan 2008) have shown that digital media technology can have myriad engaging and active learning applications. This variety reflects the variety of challenges and interests facing the teachers and students who have explored it.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have attempted to evaluate podcasting, understanding podcasting in this simple way (e.g. Abt and Barry 2007;Lazzari 2009). Such studies assume that podcasting's value lies in its capacity to reproduce existing teacher-centred models through 'coursecasting' -the practice of recording and distributing lectures (Jones 2006;Kadel 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Deal and Lazzari found no significant improvement on student grades [22,23] whereas McKinney found that students only benefitted from podcasts when they took notes and listened to the podcast many times [21].…”
Section: Discussionmentioning
confidence: 99%